PEMBERDAYAAN MASYARAKAT UNTUK MENGAKSELERASI PEMBANGUNAN DESA SUMBERGONDO BUMIAJI KOTA BATU - Rulam Ahmadi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Community service held in Sumbergondo Village, Bumiaji District, Batu District is intended to provide a set of knowledge and experience to village officials and communities so that they are more capable in developing Sumbergondo Village. This activity is carried out in the form of sharing ideas and experiences and followed by dialogue to deepen the material presented, then it can be used as one of the thinking materials in accelerating development in Sumbergondo Village. Participants at the event were generally mothers who joined the Sumbergondo Village PKK as a mobilizer for women in the village. The acceleration of development in Sumbergondo Village is important because this village is one of the villages located in the Batu City tourist area. Therefore, there needs to be continuous enlightenment so that the community is more capable of continuously participating in accelerating the development of all the potential in Sumbergondo Village